2009
DOI: 10.14712/18059694.2016.105
|View full text |Cite
|
Sign up to set email alerts
|

Scavenger Receptor CD163 and Its Biological Functions

Abstract: Summary: CD163 is a member of scavenger receptor super family class B of the first subgroup. It is mapped to the region p13 on chromosome 12. Five different isoforms of CD163 have been described, which differ in the structure of their cytoplasmic domains and putative phosporylation sites. This scavenger receptor is selectively expressed on cells of monocytes and macrophages lineage exclusively. CD163 immunological function is essentially homeostatic. It also has other functions because participates in adhesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 36 publications
2
63
0
1
Order By: Relevance
“…A 130-kDa member of the scavenger receptor cysteine-rich (SRCR) superfamily, CD163 is a single membrane-pass protein with nine extracellular domains [5]. Kristiansen et al identified CD163 as a scavenger receptor for haptoglobinhemoglobin complexes [6].…”
Section: Cd163 Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 130-kDa member of the scavenger receptor cysteine-rich (SRCR) superfamily, CD163 is a single membrane-pass protein with nine extracellular domains [5]. Kristiansen et al identified CD163 as a scavenger receptor for haptoglobinhemoglobin complexes [6].…”
Section: Cd163 Functionmentioning
confidence: 99%
“…IL-10 is involved in the polarization of macrophages to the M2 (CD163 + ) phenotype [10,11], resulting in a positive feedback loop of IL-10 and CD163 expression. However, proinflammatory signals such as tumor necrosis factor-α, interferon-γ, transforming growth factor-β, and lipopolysaccharide lead to decreased levels of CD163 expression [5].…”
Section: Cd163 Functionmentioning
confidence: 99%
“…It is present mainly on monocytes and macrophages. It has an antiinfl ammatory effect while the dynamics of its changes may be used as an indicator of infl ammatory response (10).…”
Section: Introductionmentioning
confidence: 99%
“…It is a member of the scavenger receptor cysteine-rich (SRCR) family class B. 15,16 CD163 is a 130 kDa protein consisting of 9 extracellular SRCR protein domains which are linked to a short transmembrane segment and a short cytoplasmic tail. In vitro tests have revealed that glucocorticoids, IL-10 and IL-6 increase the amount of CD163, while IL-4 and IL-13 do not raise the level of CD163 concentration, and TNF-α (tumor necrosis factor alpha), IFN-γ (interferon gamma) and CXCL4 (CXC chemokine ligand 4) decrease the concentration of CD163.…”
mentioning
confidence: 99%
“…15 In vitro studies have also shown that sCD163 secretion by monocytes and macrophages might be induced by TLR (toll-like receptor) or LPS (lipopolysaccharide). Shedding of sCD163 is equal to TNF-α response to LPS.…”
mentioning
confidence: 99%